Implementation of an Education and Early Detection Program to Reduce the Risk of Occupational Lung Disease in Furniture Craftsmen in Sambirembe Village - Ardyanto, Tonang Dwi; Myrtha, Risalina; Prabowo, Nurhasan Agung; Apriningsih , Hendrastutik; Dyanneza, Frieska; Kuncorowati, Niken Dyah Aryani; Nugroho, Novianto Adi; Suwandono, Adji; Sari, Maria Galuh Kamenyangan; Shofiyah, Laily (STMIK Widya Cipta Dharma, 2025)
Furniture industry workers in Sambirembe Village, Sragen, face significant health risks from exposure to wood dust, particularly an increased risk of Chronic Obstructive Pulmonary Disease (COPD). This research is prompted by the low awareness among workers regarding these risks and the minimal use of personal protective equipment (PPE). The objective of this program was to increase workers' and business owners' knowledge of lung health, promote early detection of COPD, and encourage the adoption of safer work practices. The method employed was an intervention that included health education and lung function screening via questionnaires and spirometry. The results revealed a critical knowledge gap, where over 85% of workers had never heard of COPD, even though 70% of them reported experiencing respiratory symptoms. Furthermore, over 90% of workers admitted to rarely using masks. The intervention, which combined education with personalized spirometry data feedback, proved effective in increasing worker awareness of tangible health risks. In conclusion, the education-based and health-screening intervention program successfully raised furniture workers' understanding of COPD risks. An approach that integrates information with personal medical evidence is crucial for promoting behavioural change in high-risk work environments.